2001
DOI: 10.1074/jbc.m101229200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of Either or Both Cys876 and Cys888 Residues of Sarcoplasmic Reticulum Ca2+-ATPase Result in a Complete Loss of Ca2+Transport Activity without a Loss of Ca2+-dependent ATPase Activity

Abstract: Disulfide-containing peptides in pepsin digest of sarcoplasmic reticulum vesicles were identified by using a fluorogenic thiol-specific reagent 4-fluoro-7-sulfamoylbenzofurazan and a reductant tributylphosphine. Sequencing of the purified peptides revealed the presence of a Cys 876 -Cys 888 disulfide bond on the luminal loop connecting the 7th and 8th transmembrane helices (loop 7-8) of the Ca 2؉ -ATPase (SERCA1a). We substituted either or both of these cysteine residues with alanine and made three mutants (C8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…The SERCA2-L4 is the longest luminal loop in SERCA2 connecting transmembrane loops M7 and M8 (7). The L4 loop of SERCA2 contains two cysteine residues, which form a disulfide bond and regulate the luminal Ca 2ϩ balance by modulating SERCA2 activity (49). A previous study in Xenopus oocytes shows that ER chaperone ER protein 57 interacts with SERCA2b in a Ca 2ϩ -dependent manner and regulates SERCA Ca 2ϩ uptake activity (16).…”
Section: Discussionmentioning
confidence: 99%
“…The SERCA2-L4 is the longest luminal loop in SERCA2 connecting transmembrane loops M7 and M8 (7). The L4 loop of SERCA2 contains two cysteine residues, which form a disulfide bond and regulate the luminal Ca 2ϩ balance by modulating SERCA2 activity (49). A previous study in Xenopus oocytes shows that ER chaperone ER protein 57 interacts with SERCA2b in a Ca 2ϩ -dependent manner and regulates SERCA Ca 2ϩ uptake activity (16).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, lumenal Loop 3-4 connected directly to M3 at the immediate C-terminal region of Ile 274 (Fig. 2) have been predicted to form the lumenal Ca 2ϩ gate (11) with essential contribution of 60). In the atomic structure E2(TG) (11) (and such interactions are less significant in E1Ca 2 structure (8)) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our results further suggested that the stabilization energy provided by intimate contacts between the three domains in E2P will provide energy for moving transmembrane helices to open the Ca 2ϩ release pathway to lumen and thus release the bound Ca 2ϩ ions. During the subsequent E2P hydrolysis to E2, the compactly organized state of cytoplasmic domains becomes more relaxed (10,11), and the postulated Ca 2ϩ release pathway (the area surrounded by M3-M5 (8)) and lumenal gate (formed with contribution of lumenal loop connecting M7-M8 (L78) (18) and possibly by its interaction with L34 (9)) should be closed to prevent possible Ca 2ϩ leakage and prepare for the entry of new Ca 2ϩ from the cytoplasmic side to the transport sites (9). In the crystal structure of E2 fixed with TG, the postulated lumenal gate and pathway are, in fact, closed (9).…”
mentioning
confidence: 99%